IMAGE AND LIDAR SEGMENTATION FOR LIDAR-CAMERA CALIBRATION (2020)
The subject disclosure relates to techniques for selecting points of an image for processing with LiDAR data. A process of the disclosed technology can include steps receiving an image data comprising an image object comprised of a plurality of image pixels, calculating a number of image pixels corresponding with the image object, receiving Light Detection and Ranging (LiDAR) point cloud data comprising a plurality of LiDAR data points corresponding with the image data collected from the camera sensor, and calculating a number of LiDAR data points corresponding with the image object. Systems and machine-readable media are also provided.